Conditional cooperation in group contests - Hubert János Kiss; Alfonso Rosa-Garcia; Vita Zhukova (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
In this paper we show experimentally that conditional cooperation, a phenomenon described in the private provision of public goods, is also present in group contests, where participants' contributions to their group performance partially determines if they overcome a rival group. This environment allows us to identify new determinants of conditional cooperation. We observe conditional cooperation in successful groups and in groups where members contribute more than rivals (even if they lose), but it vanishes in those groups that lose the contest due to low group performance. A random-effect linear panel regression analysis with an extensive set of controls confirms the findings.
Keywords: C72; C92; D70; 330; conditional cooperation; group contest